ANALISIS PENGEMBANGAN KURIKULUM SMK NEGERI 1 ENAM LINGKUNG - Netty Anggraini; Nurhizrah Gitituati; Alwen Bentri (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
The importance of education in developing human potential, improving careers, and helping realize dreams. Education is considered the foundation of culture and civilization, with the curriculum as an integral guide in the implementation of education. The curriculum is considered as a tool to achieve educational goals and determine the direction of the nation's life. Education in Indonesia receives special attention, as stated in the Preamble to the 1945 Constitution.Various efforts, such as the allocation of funds to improve the quality of education, scholarships for students and teaching staff, as well as the "freedom to learn" movement launched by the Minister of Education Nadiem Makarim, are expected to improve the quality of education. Freedom to learn aims to provide freedom of thought to teachers and students, encourage innovation and creativity in the learning process. The importance of teacher competency is also emphasized as an important factor in achieving class education and meeting international standards. International standards, such as the Program for International Student Assessment (PISA) concept, are used as a reference for measuring the quality of education. The independent learning curriculum is proposed as an important step in achieving educational goals, and its implementation at SMK Negeri 1 Enam Lingkung.